EXPERIMENTAL STUDY OF LIGHTWEIGHT REINFORCED CONCRETE HOLLOW ONE-WAY SLABS WITH PARTIALLY REPLACEMENT BY RECYCLED COARSE AGGREGATE - KAMEL, BARAA T.; Jomaa’h, MUYASSER M.; ALAZZAWI, HOSAM A. (Journal of Duhok University, 2021)
The technological development, together with the society tendency to replacing old methods through the applications of the construction materials with high efficiency, low costs and high durability by using structural thermal insulation systems, intends to increase the design age of the facilities and reduce energy consumption. Therefore, the study of light weight hollow concrete panels, becomes an important scientific goal in structural engineering. This study aimed to use lightweight and recycled materials as coarse aggregates to produce environmentally friendly concrete. Thirty-nine specimens of hollow one-way reinforced panels with dimensions (800 x 400 x 100) mm have been prepared and classified into four groups (3 panels used as reference specimens and 9 panels per each group). Claystone (ponza), thermostone aggregates, waste rubber pieces from used tires and polystyrene (cork) with volumetric replacement ratios of (25, 50 and 75) percentages of the normal aggregate were used respectively. The mechanical properties of the concrete mixtures were studied by preparing (60) samples of cylinders and prisms. The test results indicated a decrease in the mechanical properties with an increase in the percentage of lightweight coarse aggregate (25, 50 and 75 percentages). Compressive strength, tensile strength, flexural resistance and the density of the concrete test results were (10.66 – 38.44) MPa, (1.122 – 3.969) MPa, (3.606 – 10.467) MPa and (1665.5- 2426.41) kg / m3 respectively, while the ductility index in the range of (1.61-3.33). The results showed that using lightweight aggregate contributed in reducing the dead load of the proposed specimens, in addition, the best concrete mixture was that replaced by 75% of the normal aggregate with thermostone and rubber materials, as it achieved low density and acceptable compressive strength (1755.8 kg / m3 , 15.47 MPa) and (1835.5 kg / m3 , 15.47 MPa) respectively. The internal voids ratio of the sample was adopted with a total ratio of 20% of the total size of the standard sample. The results of the bending moment capacity test of the hollow panels for failure load values ranged between (23.704 – 9.259) kN for the adopted group specimens compared with the reference specimen which achieved a maximum failure load of (24.810) kN.